2018
DOI: 10.3349/ymj.2018.59.9.1096
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-128 Abates Aβ-Mediated Cytotoxicity by Targeting PPAR-γ via NF-κB Inactivation in Primary Mouse Cortical Neurons and Neuro2a Cells

Abstract: PurposeAlzheimer's disease (AD) is the sixth most common cause of death in the United States. MicroRNAs have been identified as vital players in neurodegenerative diseases, including AD. microRNA-128 (miR-128) has been shown to be dysregulated in AD. This study aimed to explore the roles and molecular mechanisms of miR-128 in AD progression.Materials and MethodsExpression patterns of miR-128 and peroxisome proliferator-activated receptor gamma (PPAR-γ) messenger RNA in clinical samples and cells were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…However, other studies have shown that a decrease in the miR-128 level significantly reduced apoptosis and caspase-3 activity in AD model on primary mouse cortical neurons and Neuro2a cells. In this model, Aβ mediated toxicity was decreased by targeting PPAR-γ via inactivation of NF-κB [120]. These results were confirmed in a mouse model of AD, where a miR-128 knockout weakened AD-like performances and reduced Aβ production and inflammatory responses by targeting PPARγ [122].…”
Section: Brain Pathology and Micrornasmentioning
confidence: 85%
See 1 more Smart Citation
“…However, other studies have shown that a decrease in the miR-128 level significantly reduced apoptosis and caspase-3 activity in AD model on primary mouse cortical neurons and Neuro2a cells. In this model, Aβ mediated toxicity was decreased by targeting PPAR-γ via inactivation of NF-κB [120]. These results were confirmed in a mouse model of AD, where a miR-128 knockout weakened AD-like performances and reduced Aβ production and inflammatory responses by targeting PPARγ [122].…”
Section: Brain Pathology and Micrornasmentioning
confidence: 85%
“…Reactive oxygen species (ROS) result in hyper-upregulation of miR-128 in cultured neurons, which suggests the possibility that microRNA may mediate ROS’s pathogenic effects in AD [119]. miR-128 is highly expressed in the hippocampus of AD patients relative to age-matched controls [120,121] and its expression is upregulated in the hippocampus in an intermediate stage of AD patients [120]. However, other studies have shown that a decrease in the miR-128 level significantly reduced apoptosis and caspase-3 activity in AD model on primary mouse cortical neurons and Neuro2a cells.…”
Section: Brain Pathology and Micrornasmentioning
confidence: 99%
“…miRNAs may participate AD pathogenesis by modulating amyloidogenic pathways: for example, miR-346 can up-regulate APP translation and Aβ production [614]. In addition, miRNAs can activate PPAR-γ, thereby stimulating NF-κB pathways to induce cytokine release and consequent Aβ production [615]. However, how a particular neurodegenerative environment within pathological contexts can alter miRNA levels, and consequential effects in modulating the miRNA milieu requires further elucidation.…”
Section: Others Factorsmentioning
confidence: 99%
“…miR-128 was reported to be overexpressed in AD patients [ 31 ]. In the present study, plasma miR-128 expression was found insignificantly higher in T2DM patients with MCI compared to T2DM patients and non diabetic individuals with normal cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MÜller and co-workers [ 32 ] reported increase expression of miR-128 in the hippocampus in an intermediate stages of AD patients and to be downregulated in late stages of AD patients. In cell cultures, inhibition of miR-128 decreases Aβ-mediated cytotoxicity through inactivation of the NF-κB pathway [ 31 ].…”
Section: Discussionmentioning
confidence: 99%